Health decentralization policy and social answer. The Colombian region case - Arango T, Gustavo; López López, María Victoria; Fernández M, Sara Yaneth; Arbeláez M, María Patricia; Gómez Tabares, Gloria Estela (Investigación y Educación en Enfermería, 2008)
During the last twenty years, social participation in Latin America, especially in Colombia has been oriented by a policy of administrative and political decentralization, with consequences in the field of health where both the state and the communities have assumed new spaces and types of relation that impact social organization and justice. Through this framework the project analyses in the Colombian region of the antioqueño southwest, some of the effects health decentralization has had taking into consideration the historic characteristics of the participation process of the population, some central aspects of the legal context of the health and social security system reforms during the last two decades, the perceptions of local actors as regards the process of the implementation of decentralized health, and the actions undertaken by the local state agents and the people in comunitary participation processes for the improvement of life and health conditions. Key Words: Health decentralization, community participation in health, social health participation, health policies, community health committees